STRUCTURE OF THE PLEISTOCENE LOESS-SOIL SEQUENCE OF WESTERN SIBERIA AND ITS CORRELATION WITH THE BAIKALIAN AND GLOBAL RECORDS OF CLIMATIC CHANGES - Dobretsov N.L.; Zykin V.S.; Zykina V.S. (My University, 2003)
In recent years, new material on the structure of the loess strata of the southern part of Western Siberia has been acquired. To date, more than 100 loess-soil sections have been studied and all pertinent published materials have been revised. Detailed correlation of these sections, based on the observation of soil horizons with similar morphotypical features on a vast territory, allowed us to refine the previously elaborated stratigraphic scheme [2] and establish a full sequence of subaerial sedimentation in the southern part of Western Siberia. The correlation of the structure of the complete loess-soil sequence for Siberia within the Brunhess chron with the structure of global continuous climatic records makes it possible not only to reveal the periodicity but also to show the compliance of climatic and environmental changes on this territory in the Pleistocene with global changes.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен